Pengaruh Foreign Direct Investment, Ekspor Barang Dan Jasa, Tingkat Inflasi Terhadap Pertumbuhan Ekonomi Di 10 Negara Asean Dalam Perspektif Ekonomi Islam - Fitri, Aliyatun; Kurniawan, Muhammad; Susanto, Is (Assyarikah: Journal of Islamic Economic Business, 2025)
Economic growth is one of the very important macroeconomic indicators, which shows the increase in the capacity of an economy to produce goods and services over time. Conceptually, this growth reflects the expansion of economic activity, which is often measured through increases in real GDP that eliminate the effects of inflation, thus providing a more accurate picture of the actual increase in production volume. This research aims to analyze and identify the effects of Foreign Direct Investment (FDI), exports of goods and services, and the inflation rate on economic growth. These three variables are considered major macroeconomic indicators that have significance. The methodology applied is a quantitative approach using regression analysis models, such as Multiple Linear Regression or panel data analysis. This model is used to test the causal relationships and significance between the independent variables (FDI, exports, and inflation) and the dependent variable (economic growth). The results of the research partially indicate that FDI has a negative but insignificant effect on economic growth, while exports of goods and services have a significant positive effect on economic growth. The inflation rate has a positive but insignificant effect on economic growth. However, in a partial manner, the three variables of FDI, Exports, and Inflation Rate together have a significant positive effect on economic growth in 10 ASEAN countries from 2018 to 2022.